2019
DOI: 10.1200/jco.2019.37.15_suppl.e14596
|View full text |Cite
|
Sign up to set email alerts
|

Role of radiomics to differentiate benign from malignant pheochromocytomas and paragangliomas on contrast enhanced CT scans.

Abstract: e14596 Background: Radiomics features, which are quantitative features generated by computational analysis of routine clinical imaging like CT scans, have been shown to be associated with clinical outcomes and tumor’s behavior in some solid tumors. We compared the radiomic features of malignant and benign pheochromocytomas/paragangliomas (P/P). Methods: Through an IRB approved study at our institution, we identified 20 consecutive patients with P/P and with available contrast-enhanced abdominopelvic CT. A rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Following manual segmentation, images were exported to the Image Biomarker Standardization Initiative (IBSI) [ 16 ] compliant software SOPHiA DDM TM Radiomics (Sophia Genetics). The patients’ CT images were resampled to a resolution of 1/1/1 mm to standardize the dataset, and grey-level quantization was performed at 32 bins prior to radiomics analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following manual segmentation, images were exported to the Image Biomarker Standardization Initiative (IBSI) [ 16 ] compliant software SOPHiA DDM TM Radiomics (Sophia Genetics). The patients’ CT images were resampled to a resolution of 1/1/1 mm to standardize the dataset, and grey-level quantization was performed at 32 bins prior to radiomics analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In recent research, O’Shea et al [ 14 ] and Cao and Xu [ 15 ] demonstrated that early-stage metastases may be differentiated from lipid-poor adenomas using contrast-enhanced CT and NECT radiomics feature–based models with high performances. In other research, radiomics was used to distinguish lipid-poor adenomas from paragangliomas, phrochromocytomas, or carcinomas [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the endpoint of interest, various ML classifiers may be used in a radiomics pipeline. Support vector machine (SVM), Bayesian network (BN), multivariate logistic regression (MLR), k-nearest neighbor (kNN), decision trees (DT), random forests (RF), neural network (NNet), and convolutional neural networks (CNN) are among the ML classifiers that are most commonly used in radiomics-based ML pipelines [8][9][10][11][12][13][14][15][16][17][18][19][20] . The feasibility of using radiomics-based ML pipelines to distinguish between benign and malignant bone lesions has been reported in previous studies 1-4, 6, 7 .…”
Section: Radiomics For Bm Detectionmentioning
confidence: 99%
“…In recent years, radiomics-based machine learning (ML) classifiers have shown great potential for use in the early detection of bone metastases (BM) and in assessing response of BM to radiotherapy (RT) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, in order to be clinically acceptable, radiomics models must be trained on large data sets of real-world images.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different studies have shown that CT texture analysis can be used to differentiate PCCs from lipid-poor adenomas [14,15]. Recently, a pilot study tested the differences between CT textural parameters in benign and malignant PCCs and paragangliomas [16]. Moreover, Ansquer et al [17] studied the application of 18F-FDG PET/CT radiomics features in the exclusive characterization of PCCs and their genetic background.…”
Section: Introductionmentioning
confidence: 99%